Multiagent Systems as an Approach to Building Fuzzy voter Communities using fuzzy languages - Milambu Belangany; Pierre Kasengadia Motumbe; Eugène Mbuyi Mukendi (Buana Information Technology and Computer Sciences)
This paper explores the use of fuzzy set theory to model the behavior of voters in a multi-agent electoral environment. Voters, represented as fuzzy agents, communicate using imprecise language to form communities based on shared linguistic terms. By leveraging graph theory, we construct a model of a fuzzy voting system where agents are linked based on the similarity of their fuzzy language. The proposed approach focuses on identifying, constructing, and extracting communities of fuzzy voters without delving into their relational dynamics. Using fuzzy set membership functions, we define linguistic variables that reflect the imprecision in voter behavior. The study introduces an algorithm to detect communities by creating links between fuzzy voters, ultimately forming groups based on their linguistic similarities. Results demonstrate that fuzzy communities can be successfully constructed, where the membership function quantifies the degree of belonging of voters to specific communities. This method contributes to a better understanding of voting behavior in complex, heterogeneous systems and offers a novel approach to community detection in multi-agent systems